2010
DOI: 10.1016/j.cmet.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acid Supplementation Promotes Survival and Supports Cardiac and Skeletal Muscle Mitochondrial Biogenesis in Middle-Aged Mice

Abstract: Recent evidence points to a strong relationship between increased mitochondrial biogenesis and increased survival in eukaryotes. Branched-chain amino acids (BCAAs) have been shown to extend chronological life span in yeast. However, the role of these amino acids in mitochondrial biogenesis and longevity in mammals is unknown. Here, we show that a BCAA-enriched mixture (BCAAem) increased the average life span of mice. BCAAem supplementation increased mitochondrial biogenesis and sirtuin 1 expression in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
514
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 490 publications
(582 citation statements)
references
References 60 publications
38
514
8
1
Order By: Relevance
“…p<0.05) (Figure 1a The in vivo findings were partially surprising because previous studies had shown that EAA nutritional supplementation stimulates mitochondrial biogenesis and endogenous defences against ROS. The consequences were: reduced cell damage, improved cellular energy production and preserved muscular structure, which finally increased life span of aged animals [1].As expected, the in vitro experiments confirmed the Doxo action on cancer cells, causing about 60% of cell death vs untreated (control) cell after 24h. On the contrary and surprisingly, EAA administration with or without Doxo, increased cancer cell mortality (Figure 1b).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…p<0.05) (Figure 1a The in vivo findings were partially surprising because previous studies had shown that EAA nutritional supplementation stimulates mitochondrial biogenesis and endogenous defences against ROS. The consequences were: reduced cell damage, improved cellular energy production and preserved muscular structure, which finally increased life span of aged animals [1].As expected, the in vitro experiments confirmed the Doxo action on cancer cells, causing about 60% of cell death vs untreated (control) cell after 24h. On the contrary and surprisingly, EAA administration with or without Doxo, increased cancer cell mortality (Figure 1b).…”
supporting
confidence: 62%
“…
CommentaryHuman and experimental data show that nutritional supplementation with a specific mixture of essential amino (EAA) improves both mitochondrial function and biogenesis and reduces either ROS formation or apoptotic drive in myocytes [1][2]. Supplementation with EAA is also effective in humans when tested in patients with cardiac dysfunction [3].
…”
mentioning
confidence: 99%
“…This was accompanied by enhanced physical endurance. Moreover, the ROS defense genes were upregulated, and ROS production was reduced [99]. EAA supplementation was also effective in reducing damage caused by alcohol in the liver and by rosuvastatin in the kidney [146,147].…”
Section: Oral Supplementation Of Special Mixture Of Aminoacids Maintamentioning
confidence: 85%
“…Indeed in these cells an increased amount of cleaved caspase 3, after treatment with AAs, was detected. In our experimental setup, the amino acids (for the detailed mixture composition see ref [99]) are provided exogenously in elevated quantities. Under these conditions the mTORC1 is activated as previously observed [100,101].…”
Section: Amino Acids Supplementation As a Cancer Fighting Weaponmentioning
confidence: 99%
“…Focal studies of several animals have shown that, by holding total caloric content constant and varying the ratio of carbohydrates and protein or key amino acids in food, individuals fed high-protein diets have much shorter lifespans than those fed diets with less protein and more carbohydrates (Miller et al 2005;Lee et al 2008;Maklakov et al 2008;Fanson et al 2009;Simpson and Raubenheimer 2009). Changes in the concentrations of specific amino acids in the diet, especially branched-chain amino acids, could also affect longevity (Alvers et al 2009;D'Antona et al 2010). Another potential explanation is that, while the food that carnivores consume better allows them to avoid conflicts between reproduction and longevity, the overall availability of this food may be lower for carnivores and, hence, limit their realized reproduction and longevity.…”
Section: Discussionmentioning
confidence: 99%